Volume 9: Ocean Renewable Energy 2015
DOI: 10.1115/omae2015-42015
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Extreme Tensions in Mooring Lines of a Floating Offshore Wind Turbine in a 100-Year Storm

Abstract: Floating offshore wind turbines (FOWTs) contribute to an emerging green energy technology, by exploiting higher and consistent wind speeds above the ocean. There are several challenges facing the design of mooring system of FOWTs, including installation costs, stability of light-weight minimalistic platforms, and shallow depths (50–300m). The extreme tension in mooring lines of a light displacement platform in shallow-water is dominated by snap loads. This is because light pre-tension requirements in the line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Fatigue damage of MoLs has been investigated by (Li et al 2018) using an Artificial Neural Network (ANN), where they observe the significant influence of the environmental conditions (waves, winds, and currents) on the tension bands. Additionally, (Hsu et al 2015(Hsu et al , 2017 demonstrate the potential benefits of using DDMs for FOWT MoLs when scaling health monitoring tools site-wide.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fatigue damage of MoLs has been investigated by (Li et al 2018) using an Artificial Neural Network (ANN), where they observe the significant influence of the environmental conditions (waves, winds, and currents) on the tension bands. Additionally, (Hsu et al 2015(Hsu et al , 2017 demonstrate the potential benefits of using DDMs for FOWT MoLs when scaling health monitoring tools site-wide.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it is possible to find a large body of work addressing MoL failures (Ma et al 2013;Davidson and Ringwood 2017;Brown et al 2005;Al-Solihat and Nahon 2018;Aranha and Pinto 2001;Bhinder et al 2015;Borg et al 2014;Hsu et al 2014Hsu et al , 2015Jin and Kim 2018;Qiao et al 2020;Maroju et al 2013;de Pina et al 2013;Prislin and Maroju 2017;Jaiswal and Ruskin 2019;Li et al 2018). The primary mechanical failure mechanisms in mooring systems are extreme load and fatigue, both of which are functions of the axial tension (Davidson and Ringwood 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Determining the extreme values of the mooring system requires effective methods to deal with the extreme analysis problem. Hsu et al (Hsu et al, 2015) presented a comparative analysis in predicting the extreme mooring line tensions of an FWT exposed to a 100-years storm condition between model test and numerical simulations. The importance of the snap events to the mooring line tensions was investigated based on the exceedance probability analysis, and results showed that normalised snap loads tend to a constant 3, which can contribute to determining the safety factor of mooring lines.…”
Section: Introductionmentioning
confidence: 99%